2019
DOI: 10.1002/mbo3.814
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of synthetic 1,3‐bis(aryloxy)propan‐2‐amines against Gram‐positive bacteria

Abstract: Synthetic 1,3‐bis(aryloxy)propan‐2‐amines have been shown in previous studies to possess several biological activities, such as antifungal and antiprotozoal. In the present study, we describe the antibacterial activity of new synthetic 1,3‐bis(aryloxy)propan‐2‐amines against Gram‐positive pathogens (Streptococcus pyogenes, Enterococcus faecalis and Staphylococcus aureus) including Methicillin–resistant S. aureus strains. Our compounds showed minimal inhibitory concentrations (MIC) in the range of 2.5–10 μg/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Structurally, the position of the chlorine is important for improving the antifungal action, since the substitution at positions meta and para of the disubstituted molecule 2j was more advantageous (lower MICs) than the substitution at ortho and para positions as for 2i (Figure ). These results corroborate the finding by Lavorato et al and Serafim et al with some compounds of the same class investigated in this study: for meta ‐substituted compounds, it was observed that the electronic effect of ring substituent has a greater influence on biological activity of this chemical class . One hundred and twenty‐one compounds were analysed in our study to follow the sequence of molecules also tested by our group for antiprotozoal and antibacterial .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Structurally, the position of the chlorine is important for improving the antifungal action, since the substitution at positions meta and para of the disubstituted molecule 2j was more advantageous (lower MICs) than the substitution at ortho and para positions as for 2i (Figure ). These results corroborate the finding by Lavorato et al and Serafim et al with some compounds of the same class investigated in this study: for meta ‐substituted compounds, it was observed that the electronic effect of ring substituent has a greater influence on biological activity of this chemical class . One hundred and twenty‐one compounds were analysed in our study to follow the sequence of molecules also tested by our group for antiprotozoal and antibacterial .…”
Section: Resultssupporting
confidence: 92%
“…for meta-substituted compounds, it was observed that the electronic effect of ring substituent has a greater influence on biological activity of this chemical class. 23,25 One hundred and twenty-one compounds were analysed in our study to follow the sequence of molecules also tested by our group for antiprotozoal and antibacterial. [23][24][25] This relevant number of synthetic compounds comprised structures of five different chemical classes with varying substituents.…”
Section: In Vitro Susceptibility and Structure-activity Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…We found dendrimers containing paracetamol groups in the outer spheres were more efficient against Gram-positive bacteria and slightly more efficacious compared to dendrimers carrying hydroxyl molecules in the periphery. It is likely that the presence of a terminal paracetamol group was responsible for the observed increase in efficacy in antimicrobial activity of their dendrimers (possibly due to target interactions with the N–H terminal group) [ 32 , 34 , 58 ]. This trend could show the action of primary amines against Gram-positive bacteria, which may also be related to the bacterial membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…However, purely synthetic antimicrobials as quinolones can also effectively inhibit bacterial pathogen growth. A synthetic approach was followed by Serafim et al, (Serafim et al, ) for synthesizing new 1,3‐bis(arloxy)propan‐2‐amines with biological activity against Gram‐positive pathogens such as Streptococcus pyogenes , Enterococcus faecalis , and S. aureus . By using docking approaches, the authors suggest that their compounds might bind to the cell division protein FtsZ.…”
Section: Commentarymentioning
confidence: 99%